2017
DOI: 10.1111/nph.14953
|View full text |Cite
|
Sign up to set email alerts
|

Nonredundant functions of Arabidopsis LecRK‐V.2 and LecRKVII.1 in controlling stomatal immunity and jasmonate‐mediated stomatal closure

Abstract: Stomatal immunity restricts bacterial entry to leaves through the recognition of microbe-associated molecular patterns (MAMPs) by pattern-recognition receptors (PRRs) and downstream abscisic acid and salicylic acid signaling. Through a reverse genetics approach, we characterized the function of the L-type lectin receptor kinase-V.2 (LecRK-V.2) and -VII.1 (LecRK-VII.1). Analyses of interactions with the PRR FLAGELLIN SENSING2 (FLS2) were performed by co-immunoprecipitation and bimolecular fluorescence complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 72 publications
(136 reference statements)
1
17
0
Order By: Relevance
“…or Alternaria brassicicola (Wang et al, 2014). LecRK-V.2, -V.5, -VI.2, -VII.1, and -IX.2 modulate PTI responses (Desclos-Theveniau et al, 2012; Singh et al, 2012; Luo et al, 2017; Yekondi et al, 2018). In rice, a cluster of three G-type LecRKs confers resistance to the phloem-sucking brown planthopper (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…or Alternaria brassicicola (Wang et al, 2014). LecRK-V.2, -V.5, -VI.2, -VII.1, and -IX.2 modulate PTI responses (Desclos-Theveniau et al, 2012; Singh et al, 2012; Luo et al, 2017; Yekondi et al, 2018). In rice, a cluster of three G-type LecRKs confers resistance to the phloem-sucking brown planthopper (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Kunkel (Washington University, St. Louis, Missouri, USA). Pst DC3000 bacteria were grown at 28°C in King's B medium supplemented with 50 mg/L rifampicin (Yekondi et al, 2017), and supplemented with 50 mg/L rifampicin and 50 mg/L kanamycin for Pst DC3000 (avrRpt2) bacteria.…”
Section: Plant and Pathogen Materialsmentioning
confidence: 99%
“…Chen (National Taiwan University, Taipei, Taiwan). B. cinerea was grown at room temperature on potato dextrose agar (PDB)agar plates as previously described (Zimmerli et al, 2001;Yekondi et al, 2017).…”
Section: Plant and Pathogen Materialsmentioning
confidence: 99%
“…Besides P2K1 (LecRK-I.9), LecRK-V.2 and LecRK-VII.1 were also reported to play essential roles in regulating stomatal closure (Yekondi et al, 2018). Recently, it was reported that P2K1 is involved in modulation of jasmonic acid (JA)-mediated gene expression for plant defense responses (Tripathi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%